Women’s empowerment, incomes and resilience in agri-food systems - Phillips, Lauren M.; Anteneh, Zecharias; Cavatassi, Romina; Mabiso, Athur; Maggio, Giuseppe (Food and Agriculture Organization of the United Nations, 2023)
Women’s empowerment is a fundamental objective in itself and in generating positive results for their households. In the existing literature on women’s empowerment in the context of agriculture and agrifood systems there is a dearth of evidence regarding impact on livelihood outcomes, income and resilience to shocks. To address this research gap, the paper analyses the role of development projects which focused on women’s empowerment in the agriculture and agri-food on household income and resilience. The analysis utilizes a comprehensive pooled dataset from the International Fund for Agricultural Development (IFAD), consisting of 24 IFAD rural development projects. In our analysis we identify treatment and comparison groups by distinguishing two types of projects: projects that improve women’s decision-making power over the use of income and/ or resources, and projects that do not contribute to such improvement—an important indicator of agency and empowerment. We find that there are appreciable benefits for household income and resilience in a significant number of households were women report an improvement in their empowerment. Building on this classification, the study extrapolates the achieved results to the entire investment portfolio and simulates the potential outcomes if all projects were focused on women’s empowerment. Furthermore, the study calculates the achievable results in a scenario where investments of this nature cover half of the intended beneficiaries, estimating the corresponding impacts on income generation and resilience. Overall, this research highlights the critical role of women’s empowerment in driving positive outcomes in agriculture, rural development, and the livelihoods of small-scale producers.